Loss of the E3 ubiquitin ligase HACE1 results in enhanced Rac1 signaling contributing to breast cancer progression - Goka, E T (Oncogene, 2015)
The transition from ductal carcinoma in situ (DCIS) to invasive breast cancer (IBC) is a crucial step in breast cancer progression. The specific alterations that govern this transition have not been elucidated. HER2/neu is frequently overexpressed in DCIS but is less common in IBC, thereby suggesting additional requirements for transformation. To identify genes capable of cooperating with HER2/neu to fully transform mammary epithelial cells, we used an insertional mutagenesis screen on cells isolated from wild-type neu expressing mice and identified the E3 ligase HACE1 as HER2 cooperative tumor suppressor gene. Loss of HACE1 expression is commonly seen in clinical breast cancer data sets. HACE1 downregulation in normal human mammary epithelial cells (HMECs) results in the accumulation of the activated GTP-bound Rac1 partially transforming these cells. Overexpression of HER2 activates Rac1, which further accumulates upon HACE1 loss resulting in Rac1 hyperactivation. Although the knockdown of HACE1 or overexpression of HER2 alone in HMECs is not sufficient for tumorigenesis, HER2 overexpression combined with HACE1 downregulation fully transforms HMECs resulting in robust tumor formation. The pharmaceutical interference of Rac function abrogates the effects of HACE1 loss both in vitro and in vivo, resulting in marked reduction in tumor burden. Our work supports a critical role for HACE1 in breast cancer progression and identifies patients that may benefit from Rac-targeted therapies.